Worldmark modern conflict and diplomacy - Johnson, Cynthia 1969- (Detroit Gale Cengage Learning, 2014)
"Worldmark Modern Conflict and Diplomacy presents easy-to-understand information on 90 global conflicts and diplomatic efforts in 2 volumes. The set will cover specific conflicts that have had a truly global impact, as well as the efforts and organizations focused on solving these conflicts. Arranged alphabetically, each of the approximately 90 entries will cover the origins of a conflict or diplomatic effort, its current status, and its wide-ranging impact on the world. Topics include historical and current conflicts from World Wars I & II to Al-Qaeda and the Arab Spring, as well as diplomatic efforts such as the United Nations and the Nobel Peace Prize. The set includes material on recent events in places ranging from Kosovo to Myanmar to South Sudan to the Palestinian Territories"-- Provided by publisher.
Volume 1. A-I -- Volume 2. J-Z.
Includes bibliographical references (pages xxxv-xli) and index.
Keywords: International relations -- History -- 20th century -- Encyclopedias -- Juvenile literature; International relations -- History -- 21st century -- Encyclopedias -- Juvenile literature; Diplomacy -- History -- 20th century -- Encyclopedias -- Juvenile literature; Diplomacy -- History -- 21st century -- Encyclopedias -- Juvenile literature; World politics -- 20th century -- Encyclopedias -- Juvenile literature; World politics -- 21st century -- Encyclopedias -- Juvenile literature; Military history -- 20th century -- Encyclopedias -- Juvenile literature; Military history -- 21st century -- Encyclopedias -- Juvenile literature